ANALISIS KLAUSUL PERJANJIAN TABUNGAN HAJI ANTARA NASABAH DAN BANK KALBAR CABANG SYARIAH PONTIANAK PERSPEKTIF FATWA MUI - Syarif Hidayatullah; Rusdi Sulaiman; Nur Rahmiani (Al-Aqad, 2023)
The purpose of this research is to determine the content of the Hajj savings agreement clause between customers and Bank Kalbar Pontianak Syariah Branch. This research uses legal research methods and normative research types using library data collection methods. Research data sources are primary and secondary. Data collecting techniques are bibliography study, document study, and documentation. Data analysis techniques use contract interpretation and systematization techniques. According to the results of the research conducted, the researcher can conclude that: 1) In the content of the Hajj Savings Agreement clause between the customer and Bank Kalbar Syariah Branch Pontianak, which contains the content of the Hajj Savings Agreement clause regarding the rights and obligations between the customer and the bank. 2) The basis for the preparation of the contents of the Hajj Savings Agreement Clause at the Pontianak Syariah Branch of Bank Kalbar, namely with reference to the DSN-MUI Fatwa, POJK No.13 / POJK.03 / 2021 on the implementation of commercial banking products, and Law No. 21 of 2008 on Islamic Banking 3) As for the analysis of the contents of the Hajj savings agreement clause between the customer and Bank Kalbar Syariah Branch Pontianak, overall the contents of the clause are consistent and in accordance with the provisions of the DSN-MUI fatwa.